Stereotactic Body Radiotherapy Immunological Planning—A Review With a Proposed Theoretical Model - Swamy, Kumara (Frontiers in Oncology, 2022)
In the stereotactic body radiotherapy (SBRT) and immunotherapy era, we are moving toward an “immunological radiation plan,” i.e., radiation scheduling with abscopal effect as a vital endpoint as well. The first part of this article reviews existing data favoring the factors maximizing the immune activation with SBRT and forms the foundation for the theoretical models presented in the second part. Advantages of intermediate dose of SBRT 6 - 10 Gy per fraction, appropriate use of dose painting, proper timing with immunotherapy, and potential of immune-adjuvants are discussed. Current literature favors that immunotherapy should not precede but follow soon after SBRT. The importance of proton, carbon-ion SBRT is dealt with briefly. The second part proposes tumor vasculature integrity being the central theme for converting “abscopal effect by chance” to “abscopal effect by design” using a harmonized combinatorial approach. Towards this end, these theoretical models depict optimization of the outcome of abscopal response in SBRT, based on the principle of the well-known five R’s of radiotherapy. Included is the possible role of integrating “cyclical” antiangiogenics, immune adjuvants/immune-metabolites as abscopal effect enhancers with SBRT, and suggestion for convergence in further research keeping normalization of tumor vasculature as the central focus.